Flexible diphenylsulfone versus rigid dibenzothiophene-dioxide as acceptor moieties in donor-acceptor-donor TADF emitters for highly efficient OLEDs - Gudeika, Dalius; Lee, Jiun Haw; Lee, Peihsi; Chen, Chiahsun; Chiu, Tienlung; Baryshnikov, Gleb V.; Minaev, Boris F.; Ågren, Hans S.; Volyniuk, Dmytro; Bezvikonnyi, Oleksandr; Grazulevicius, Juozas V. (Elsevier B.V., 2020)
Flexible versus rigid molecular structures of donor-acceptor-donor type compounds are investigated with respect to efficiency of thermally activated delayed fluorescence (TADF) by theoretical and experimental approaches. Three highly efficient TADF emitters based on flexible diphenylsulfone and rigid dibenzothiophene-dioxide as acceptor units and di-tert-butyldimethyldihydroacridine as donor moiety were designed and synthesized. Despite they showed similar singlet-triplet splitting (0.01–0.02 eV) and high photoluminescence quantum yields in appropriate hosts, maximum external quantum efficiencies as different as 24.1 and 15.9/19.4% were obtained for organic light emitting devices based on these emitters with, respectively, flexible and rigid molecular structures. The high efficiency of the light-emitting compounds with the flexible molecular structure could be traced to the bi-configurational nature of the lowest singlet and triplet states resulting in higher spin-orbit coupling than for molecules with rigid structures. All derivatives showed bipolar charge transport character. High device efficiency with electron mobility of 3 × 10−5 cm2V−1s−1 and hole mobility of 1.3 × 10−4 cm2V−1s−1 at the electric field of 5 × 105 Vcm−1 was recorded for the layer of para-disubstituted diphenylsulfone with flexible molecular structure. This TADF emitter showed an excellent performance in the organic light emitting device, exhibiting a maximum current efficiency, power efficiency, and external quantum efficiency of 61.1 cdA-1, 64.0 lmW−1, and 24.1%, respectively.
DG acknowledges funding from the ERDF PostDoc project No. 1.1.1.2/VIAA/1/16/177 . This research is/was funded by the European Regional Development Fund according to the supported activity ‘ Research Projects Implemented by World-class Researcher Groups ’ under Measure No. 01.2.2-LMT-K-718 . Ministry of Science and Technology (MOST), Taiwan , Grant No. MOST 106-2923-E-155-002-MY3 . This work was also supported by the Ministry of Education and Science of Ukraine (projects no. 0117U003908 and 0118U003862 ), and by the Olle Engkvist Byggmästare foundation (contract No. 189-0223 ). The quantum-chemical calculations were performed with computational resources provided by the High Performance Computing Center North (HPC2N) in Umeå, Sweden, through the project ‘‘Multiphysics Modeling of Molecular Materials” SNIC 2018-2-38.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Bipolar charge transport; di-tert-butyldimethyldihydroacridine; Dibenzothiophene dioxide; Diphenylsulfone; Thermally activated delayed fluorescenc